Pelatihan Pembuatan Video Pembelajaran Menggunakan Aplikasi AZ Screen Bagi Guru Bidang Studi Ekonomi SMA di Kabupaten Sijunjung Sumatera Barat - Zul Afdal; Rino; Armida (Manaruko: Jurnal Pengabdian Masyarakat, 2022)
This community service amis to improve teachers' comprehension and awareness of the value of learning media in instructional activities. Additionally, Sijunjung West Sumatra High School teachers are trained by this initiative to create instructional films utilizing the AZ Screen Application. Increased teacher creativity in the creation and use of video learning material is the specific goal to be met in order to make economic education in schools more relevant. Counseling, instruction, and question-and-answer techniques are the approaches employed in the delivery of this service. At the first week of this activity, observations are made in schools and other relevant institutions/agencies. carried on with the essential tasks. Making educational movies with the help of the AZ Screen application for instructors is the main activity, which takes the shape of socializing exercises. Activities can broaden instructors' understanding of the importance of learning media and the evolution of learning media, particularly as they relate to technological advancements. Teachers' computer or smartphone skills, particularly their ability to load material using the AZ Screen app, have also improved thanks to this exercise.